2008
DOI: 10.1002/cnm.1131
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioners for the indefinite linear system arising from the hp discretization of Maxwell's equations

Abstract: SUMMARYThis paper describes a preconditioner for the iterative solution to the indefinite linear equation system that is obtained when the vector wave equation is discretized by higher-order H(curl)-conforming finite elements. The preconditioner is based on a decomposition of the H(curl)-conforming functions into blocks comprising lower-order functions and higher-order functions. Fast convergence is obtained when the grid spacing is sufficiently small. A method for selecting suitable grid spacings is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…In the above, B D A C jÄjM and Q B follow from the static condensation of the interior block of B in the fictional linear system By D 0. The reason for following this approach is that the resulting blocks Q B EE and Q B FF are then positive definite (Ledger, 2009). If an additional decomposition of the face functions into gradients and nongradients is undertaken, the block associated with the gradient face functions can then be treated in similar way as the high order edge block in Eq.…”
Section: Ingredients For the Preconditioner For Three-dimensional Promentioning
confidence: 98%
See 3 more Smart Citations
“…In the above, B D A C jÄjM and Q B follow from the static condensation of the interior block of B in the fictional linear system By D 0. The reason for following this approach is that the resulting blocks Q B EE and Q B FF are then positive definite (Ledger, 2009). If an additional decomposition of the face functions into gradients and nongradients is undertaken, the block associated with the gradient face functions can then be treated in similar way as the high order edge block in Eq.…”
Section: Ingredients For the Preconditioner For Three-dimensional Promentioning
confidence: 98%
“…In Ledger (2009), numerical results were presented that showed that the eigenvalues of the preconditioned system became clustered about a point bounded away from zero once the mesh spacing was sufficiently small. In this section, a detailed investigation of the eigenspectrum of the preconditioners proposed in Eqs.…”
Section: Analysis Of the Eigenspectrum For Quadrilateral Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hierarchic basis functions proposed by Schöberl and Zaglmayr lend themselves to a parameter-robust iterative two-level solver: Assuming that an appropriate h-version solver on the low-order space (the coarse level) is available, simple block Jacobi smoothing is sufficient on the high-order level (the fine level). This preconditioning technique is described and analysed in [65,78] and has been modified for wave propagation problems by Ledger [48,47]. In this work, we combine and extend these strategies by further exploiting the discrete space splitting of the underlying hierarchical hp-finite element basis and suggest an improved version of a hierarchical hp-finite element solver for eddy current problems.…”
Section: Introductionmentioning
confidence: 99%